Palaeontology and Depositional Setting of Chert Member, Semanggol Formation, North Kedah - Binti Nordin, Nurfaradine (Universiti Teknologi PETRONAS, 2016)
Thirty one radiolarians taxa were retrieved from chert samples collected from the Semanggol Formation at Kampung Rambutan in district of Pokok Sena Kedah. Pokok Sena area is bounded by the latitude form 100° 34’ 00° E to 100° 36’ 00º E and from 006° 13’ 00º N to 006° 14’ 00° N which is about 48km². The radiolarians consist of Pseudoalbaillella cf. scalprata, Pseudoalbaillella cf. lomentaria, Entactinia sp., Quinqueremis sp., Ruzhencevispongus sp. and Neoalbaillella cf. optima. Significantly the study location is identified to be Early Permian to Late Permian in age by the assemblage of Pseudoalbaillella scalprata m. rhombothoracata Zone Ishiga and Neoalbaillella optima Zone Kuwuhara. The assemblages indicate the depositional environment was a deep marine basin below the carbonate compensation depth.